Selection of Recommended Marketing Strategy of Arrowroot Cereal at PT Serela Prima Nutrisia Using Analytical Hierarchy Process - Budiarto budiarto; Stefanus Dannydra Prasetyo (CV. Publikasi Indonesia, 2023)
PT Serela Prima Nutrisia is a company engaged in the arrowroot (Maranta Arundinacea)-based processing product. (1) This research aimed to identify and analyze alternative strategies that could be applied in Oriflakes marketing activities and (2) to identify the company’s marketing strategy that could be recommended according to the segmentation, targeting, and positioning. This research used a descriptive approach. The location determination method used case studies whereas the determination of the respondents used a purposive method. Types of data used in this research were primary and secondary data. The data collection methods used in this research were observation, interviews, documentation, recording, and questionnaires. The analytical techniques used in this research were Descriptive Analysis, Internal and External Factors Matrix, IE Matrix (Internal External), and AHP (Analytical Hierarchy Process). The results from this research showed that the marketing mix applied by the company were product, price, promotion, place, and the STP concept, which were segmentation, targeting, and positioning. The results from the IE matrix showed that the company position was on hold and maintain. The results of the AHP matrix showed that the highest socre was obtained on the product development strategy. An alternative strategy recommended for the company was a product development strategy.